2011
DOI: 10.1097/brs.0b013e3181d952c2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neck and Low Back Pain in Community-Dwelling Adults in Spain

Abstract: This Spanish population-based survey showed that neck and low back pain are prevalent and highly associated between them, more frequent in female (particularly neck pain) and associated to worse self-reported health status. Individuals with neck and low back pain were more likely than those without pain to have depression and other painful conditions, including headache and osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
3
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 28 publications
(51 reference statements)
11
109
3
12
Order By: Relevance
“…Women presented a higher prevalence of back pain than men, with statistical significant difference (p = 0.001), similar to studies conducted in England (14) and Spain (16). However, such results are not consistent.…”
Section: Resultscontrasting
confidence: 44%
“…Women presented a higher prevalence of back pain than men, with statistical significant difference (p = 0.001), similar to studies conducted in England (14) and Spain (16). However, such results are not consistent.…”
Section: Resultscontrasting
confidence: 44%
“…Chronic pain is more frequent in females, older adults, and manual workers, and people who are obese, smoke, and/or 2 www.spinejournal.com xxxx 2014 lead a sedentary lifestyle as well as in individuals with poorer overall health. [7][8][9][10][11] On the contrary, absenteeism is more frequently associated with younger age, higher income, higher education, and worse self-reported health status. 10 , 12 , 13 This study examined the relationship between 3 prevalent types of chronic pain, the occurrence of absenteeism, and the number of days absent from work in the last year in a nationwide representative sample of Spanish workers.…”
mentioning
confidence: 99%
“…A recent Danish study concluded that disabling low back pain is exceedingly rare before the age of 50 17 , while a North--American group reported that general disc diseases were the most important cause of low back pain in middle-aged adults 18 . Another recent paper, this time from Spain, discusses the high prevalence of low back pain in several age groups, highlighting the low quality of life and high levels of depression in those individuals suffering from spinal pain 19 . It is therefore relevant to have Brazilian studies analyzing the prevalence and characteristic of middle aged adults with low back pain in different regions of the country.…”
Section: Discussionmentioning
confidence: 99%